SUSTAINABLE RECYCLING OF POLYETHYLENE WASTE THROUGH UTILIZATION IN ASPHALT PAVING APPLICATIONS - Jamil, Mohammed G.; Salih, Oday A.; Hameed, Ayman Talib; A.I., Al-Hadidy (Journal of Applied Engineering Science, 2023)
One the enormous amount of waste polyethylene (PE) materials amassing in Iraq is posing an expensive landfill and disposal issue. The current study examines the potential for employing PE as a partial replacement for environmentally friendly pavement construction. Different amounts of PE were used to partially replace asphalt cement (3 %, 6 %, 9 %, and 12 % by weight). The PE-substituted asphalt (PESA) binders were subjected to the rheological and compatibility properties. Additionally, two asphalt concrete (AC) mixtures—one control and one PEAC—were created for the mechanical and durability experiments. Among the parameters assessed during the tests are the following: adhesion to a variety of substrates and substrate surfaces; elongation at room temperature (aging index); flexibility at elevated temperatures (cracking index); temperature susceptibility; compatibility; and the extensional viscosity of the PESA binder as well as the extensional viscosity of the PESA-mixture (PESAM). Furthermore, the mechanical and durability properties of AC and PEAC mixes were examined using the Marshall stability, Marshall quotient, static indirect tensile strength at 25 and 60°C, tensile strength ratio, and resilient modulus 25°C tests. Results show that PESA binder outperforms virgin asphalt binder in terms of cracking and temperature resistance. PEAC mixture exhibits higher stability, indirect tensile strength, moisture resistance and resilient modulus than AC mixture. According to standard and durability testing, replacing virgin binder with six percent PE can be recyclable and suitable for use as sustainable material for paving applications.